Arching from Function to Form-Important Design Elements of Simulation Exercises (SimEx) in Emergency Response and Disaster Risk Management - Andra Iustina Covaciu; Marcus Abrahamsson; Albrecht Beck; Shivani Rai; Niroj Sapkota; Mark Shapiro; Joerg Szarzynski (MDPI AG, 2021)
With Rasmussen's abstraction hierarchy as starting point, the present article focuses on understanding some of the aspects guiding the development of a simulation exercise (SimEx) from a multi-faceted perspective, based on interviews and post-exercise evaluations conducted with both exercise designers and participants. The results show that, in order to achieve its overarching objective, an exercise must fulfill a wide range of "functions", which in turn can take various kinds of "forms" or actual representations in the physical world. The paper discusses a number of identified required functions of a SimEx, sometimes labeled as design elements, and furthermore elaborates on differences and specific requirements at form level, e.g., virtual vs. physical exercises.